2009
DOI: 10.1590/s1516-35982009000800010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da interação genótipo-ambiente e comparação entre modelos para ajuste do ganho pós-demama de bovinos Devon via normas de reação

Abstract: RESUMO -Os objetivos com este estudo foram verificar a presença de interação genótipo-ambiente e comparar modelos para o ajuste do ganho pós-desmama padronizado para 345 dias de bovinos da raça Devon, via normas de reação obtidas por regressão aleatória. Genotype by environment interaction characterization and model comparison for post weaning gain adjustment of Devon cattle via reaction normsABSTRACT -The objectives of this study were to verify the presence of the genotype by environment interaction and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
2
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
4
14
2
12
Order By: Relevance
“…For the two-step model -the second best model -the correlations also displayed greater variation (−0.79 to 1.00), which denotes GEI. The results obtained herein indicate that the genetic material necessary for production in various environmental levels must be different, even if partially, and differ only in magnitude from those presented by Corrêa et al (2009), who observed the negative genetic correlations among environmental gradient levels for standardized post-weaning gain at 365 days. Mattar et al (2011) observed higher values than those in the present study (0.24 to 1.00).…”
Section: Resultscontrasting
confidence: 73%
“…For the two-step model -the second best model -the correlations also displayed greater variation (−0.79 to 1.00), which denotes GEI. The results obtained herein indicate that the genetic material necessary for production in various environmental levels must be different, even if partially, and differ only in magnitude from those presented by Corrêa et al (2009), who observed the negative genetic correlations among environmental gradient levels for standardized post-weaning gain at 365 days. Mattar et al (2011) observed higher values than those in the present study (0.24 to 1.00).…”
Section: Resultscontrasting
confidence: 73%
“…The heritabilities found in those studies increased as the environment became more favorable (Fikse et al, 2003;Shariati et al, 2007;Corrêa et al, 2009;Pégolo et al, 2009;Strandberg et al, 2009). …”
Section: Resultsmentioning
confidence: 91%
“…Some studies have used reaction norm models to evaluate the presence of GxE effects (Corrêa et al, 2009;Pégolo et al, 2009). These norms describe the expression of a genotype as a linear function (reaction norm) of an environmental value or gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the existence of G*E interaction was verified in the Devon cattle population of Rio Grande do Sul State in Brazil (Corrêa et al, 2009). These authors observed that the reaction norms model with homogeneous residual variance was the best fit to the post-weaning gain data compared to the reaction norms model with heterogeneous residual variance and the animal model, traditionally used in genetic evaluations.…”
Section: Introductionmentioning
confidence: 99%